The Connection Between the Crime of Trading in Influence and Gratification in Corruption - Setyawan, Vincentius Patria (Talenta Publisher, 2025)
Corruption poses a persistent threat to the foundations of good governance and public integrity. One of the common modes used in corruption practices is trading in influence and gratification. Trading in influence occurs when a person leverages their influence over a public official to obtain certain benefits; unlike bribery, the object of trading in influence is influence itself, not direct authority. Meanwhile, gratification encompasses all forms of gifts or benefits that may affect the independence of officials in making decisions. Both practices have the potential to undermine bureaucratic systems and diminish public trust in the government. This study aims to analyze the correlation between trading in influence and gratification as forms of corruption, as well as to review their impact and implications on the legal and governmental system. The research method used is a normative juridical approach, analyzing relevant legislation and case studies of corruption incidents involving these two practices. The results show that trading in influence and gratification often serve as the entry points for more severe corruption practices. In this context, Article 18 of the UNCAC provides an important conceptual basis for the development of national legal norms to specifically define and address trading in influence. Therefore, there is a need for stronger regulations and more effective law enforcement to prevent and combat these practices